LEGAL PROTECTION OF CHILDREN AS WORKERS IN THE FISHERIES SECTOR: A CASE STUDY OF MEDAN BELAWAN DISTRICT - Medelin Lubis; Faisal Riza (Inspiring Law Journal, 2026)
This study examines the phenomenon of child labor in the fisheries sector in Medan Belawan District, which is triggered by poverty and low educational motivation. Although national regulations prohibit child exploitation, this practice continues due to weak oversight and cultural normalization. Using a normative-empirical legal research method with an empirical juridical approach, data were collected through on-site observation and interviews. The results show that legal protection is normatively regulated in Law No. 35 of 2014 and Law No. 13 of 2003, but its implementation has not been effective due to internal (economic and educational) and external (cultural and weak oversight) barriers. A synergy of preventive measures and firm repressive measures is needed to guarantee children's rights in coastal areas.